Education for Students with Special Needs: Child X Case - Kontautaitė, Monika; Norvilienė, Aida (Vilnius University Open Series, 2020)
The article presents the opinion of teachers and parents concerning the educational situation of students with special educational needs at general education schools. The qualitative research, which was carried out by means of a semi-structured interview with teachers and parents, helped to determine that students with special educational needs are included in the general education school on a theoretical rather than practical basis. Despite the fact that the school advocates the inclusion of students with special educational needs and provides various special support services, informants observe a number of weaknesses in the system that do not provide an opportunity for the subject to receive the support one requires. It is alleged that teachers working at general education schools are not trained to work with such students and there is a lack of means and facilities for individual work. There are too many students in classes. Due to the following reasons, education that the subject receives is not always efficient. It was also revealed that specialists working with the subject have difficulties in communicating with each other and working as a team in order to set and achieve a common goal. All interviewees work as they think is best. Poor parent-subject work at home was also emphasized. For the given reasons, there is a lack of continuation in the education of the subject, which is one of the most important factors influencing the educational success of students with special educational needs.